Etno-Agronomi Budidaya Kopi yang Toleran Variabilitas Curah Hujan - Rusdi Evizal; Fembriarti Erry Prasmatiwi; Setyo Widagdo; Hery Novpriansyah (Politeknik Negeri Lampung, 2020)
West Lampung Regency still survives as the central area of coffee production in Lampung Province while production of other districts so far are declining. This research aims to study the ethno-agronomy of coffee cultivation in West Lampung which is tolerant to rainfall variability. This research was a survey located in Sumberjaya District and Sekincau District, West Lampung Regency, Lampung Province, Indonesia year 2018—2019 which from each subdistrict two villages was selected purposively and from each village one farmer group was chosen. Primary data were collected through interview, Focused Group Discussion (FGD), and observation of coffee farm. Secondary data were obtained from the BPS Lampung and rainfall data from Radin Intan Climate Station. The results showed that the area of coffee plantations in West Lampung in the last decade has decreased by 0,64% per year but productivity has increased by 1,42% per year, and in West Lampung, which is a mountainous region, the number of rainy days was negatively correlated with coffee yield while the number of dry months was positively correlated. Whereas in North Lampung, which is a medium elevation area, coffee productivity correlated with sufficient rainfall and productivity was negatively correlated with the number of dry months of the previous year. Coffee farmers in West Lampung have perception the need for various adaptation measures of coffee farm maintenance, which grafting adult coffee tree with superior local robusta clones is a typical ethno-agronomy practiced by coffee farmers in West Lampung to obtain high coffee yield.